LEVERAGING STANDARDIZED PUBLIC TRANSPORTATION DATA WITH ROUTING ENGINE FOR BRT TRIP PLANNER PROTOTYPING - Alghifari Fauzta, Rayhan
Public transportation is an essential aspect to consider in the effort towards sustainable city development. A widely developed public transport mode in major cities is the Bus Rapid Transit (BRT) system. However, BRT systems are prone to schedule deviations. Passengers may also be inconvenienced if they lack access to real-time information such as bus positions and arrival times. One solution to this issue is the presence of information systems for passengers through trip planning applications. While such solutions already exist, an often overlooked aspect is the availability and openness of public transportation data through open data. This research discusses the standard for open data exchange for BRT information through the implementation of a web-based trip planner prototype. The open data standards used are the General Transit Feed Specification (GTFS) for static data and GTFS Realtime for real-time data. Data is sourced from the open data of the MTA transportation operator in New York City, USA. The routing engine tool on the backend side uses OpenTripPlanner (OTP), and the user interface utilizes Redux OTP and React OTP-UI components. Implementation involves data acquisition into the routing engine system integrated with the interface through GraphQL data fetching methods. The generated travel recommendations include real-time service disruption information, estimated arrival times at stops, and bus positions updated every 60 seconds. Functional testing results show that the relevant functional requirements for BRT passengers are met through the implementation of GTFS data standards in the prototype. Testing was also conducted using GTFS data sources from the Transjakarta operator and the TriMet operator in Portland, USA. The results indicate that the prototype can accept data from different operators as long as it is in GTFS format, demonstrating the prototype's flexibility and significant potential for further development.